2013
DOI: 10.1371/journal.pone.0068214
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Calcium Chloride on Growth, Photosynthesis, and Antioxidant Responses of Zoysia japonica under Drought Conditions

Abstract: Few attempts have been made to study the alleviating effects of signal molecules on zoysiagrass ( Zoysia japonica ) under drought stress. Calcium chloride has been shown to ameliorate the adverse effects of drought stress on many plants. It is necessary to investigate how to enhance drought tolerance of zoysiagrass using calcium chloride. The study elucidated the effects of calcium chloride on zoysiagrass under drought conditions by investigating the following parameters: biomass, chlorophyll (Chl) content, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 46 publications
8
70
0
6
Order By: Relevance
“…status influences plant productivity as well as tolerance to both biotic and abiotic stresses; thus, plants with calcium deficiencies are more susceptible to pathogens and osmotic stress (Bangerth 1979;Marchner 1995;Sanders et al 1999;Knight 2000). Indeed, CaCl 2 has been shown to improve stress tolerance in many studies (Xiang et al 2008;Jaleel et al 2007;Upadhyaya et al 2011;Ma et al 2005;Xu et al 2013).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…status influences plant productivity as well as tolerance to both biotic and abiotic stresses; thus, plants with calcium deficiencies are more susceptible to pathogens and osmotic stress (Bangerth 1979;Marchner 1995;Sanders et al 1999;Knight 2000). Indeed, CaCl 2 has been shown to improve stress tolerance in many studies (Xiang et al 2008;Jaleel et al 2007;Upadhyaya et al 2011;Ma et al 2005;Xu et al 2013).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Calcium plays a central role in many defense mechanisms that are induced by drought; these mechanisms can be either structural, for example, leading to increased cell wall integrity (Guimarães et al 2011), or may elicit a signaling response (Xu et al 2013). An increase in external Ca 2?…”
Section: Divalent Cation Accumulationmentioning
confidence: 99%
“…Various studies conducted on different plants have revealed that CaCl 2 acts as a physiological treatment to enhance stress tolerance (Tan et al, 2011;Xu et al, 2013). Addition of exogenous calcium has also been found to enhance salt tolerance (Hifney, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ca is involved in the regulation of various processes in response to abiotic stresses, e.g., of stomatal regulation mediated by the hormone ABA (Song et al, 2008), antioxidant enzyme activities (Jiang and Huang, 2001) and photosynthetic rates (Xu et al, 2013). Calcium also plays a fundamental role in the resumption of tree cambium growth (Fromm, 2010) and in dry matter increases of E. camaldulensis (Oliva et al, 1995) during water stress.…”
Section: Introductionmentioning
confidence: 99%